2019
DOI: 10.1016/j.heliyon.2019.e02723
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic triplet of Colombian sawmill wastes using thermogravimetric analysis

Abstract: The potential of sawmill wastes as a raw material in pyrolysis process is presented in this study. Non-isothermal thermogravimetric analysis (TGA and DTG) and isoconversional methods were employed to determine triplet kinetic (activation energy, reaction model and pre-exponential factor). Through TGA and DTG, the conversion degree is described as a function of temperature for five heating rates (10, 20, 30, 40 and 50o C/min) and four model-free methods (Flynn-Wall-Ozawa (FWO), Kissinger-Akahira-Sunose (KAS), F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Usually, the kinetics study is divided into 2 categories: model-free and model-fitting method. Model-free or iso-conversional such as the Kissinger-Akahira-Sunose, Flynn-Wall-Ozawa, and Coats-Redfern methods is usually easier to be applied since it only requires contemporary linear regression which does not require a high computational cost [ 24 , 25 , 26 ]. However, most of the model-free methods usually needs a minimum of 3 experiments at different heating rates to be applied accordingly [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually, the kinetics study is divided into 2 categories: model-free and model-fitting method. Model-free or iso-conversional such as the Kissinger-Akahira-Sunose, Flynn-Wall-Ozawa, and Coats-Redfern methods is usually easier to be applied since it only requires contemporary linear regression which does not require a high computational cost [ 24 , 25 , 26 ]. However, most of the model-free methods usually needs a minimum of 3 experiments at different heating rates to be applied accordingly [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5B 27 Furthermore, Yao et al reported an average activation energy of 169.9 kJ•mol −1 using the FWO method. 26 The reason behind such deviations may be due to the fact that the TGA experiments were carried out at very low heating rates (0.5, 1, and 2°C•min −1 ) in this study as compared to those utilized by Gupta et al (5,10,15,20, and 30°C•min −1 ), Chen et al (15,25,35,45, and 55°C•min −1 ), as well as Yao et al (2, 3.5, 5, 7.5, 10, and 15°C•min −1 ), allowing for a larger dataset. Another explanation regarding the deviation in results can be related to the inherent characteristics of the cotton stalks used for analysis.…”
Section: Kinetic Modeling Resultsmentioning
confidence: 86%
“…7 The main model-free methods discussed in the literature include ASTM-E698, which is a model-free noniso-conversional approach, the Flynn-Wall and Ozawa (FWO), and Kissinger-Akahira-Sunrose (KAS), which are categorized as integral iso-conversional methods, and the Friedman method which is a differential iso-conversional method. [6][7][8][9][10][11][12][13] The main issue related to the ASTM-E698 method is that a single activation energy value is calculated, not considering reaction progress in such a complex thermochemical process. It is more suitable for a single-step reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Model fitting techniques are, in general, not recommended by the international confederation for thermal analysis and calorimetry (ICTAC) kinetics committee due to the uncertainty related to the determination of kinetic parameters (Vyazovkin et al 2011). The most common model-free methods reported in the literature include the single-step reaction method ASTM E-698, integral iso-conversional methods such as Flynn-Wall-Ozawa, and Kissinger-Akahira-Sunose and Friedman's differential iso-conversional method (Osman et al 2020b, c;Akor et al 2021;Mishra and Mohanty 2018;Luo et al 2020;Bonilla et al 2019). In general, all methods carry various drawbacks and may lead to errors and inaccuracies in computing kinetic parameters if mishandled (Vyazovkin et al 2011;Luo et al 2020).…”
Section: Thermo-kinetic Analysismentioning
confidence: 99%